1994
DOI: 10.1523/jneurosci.14-11-06317.1994
|View full text |Cite
|
Sign up to set email alerts
|

Selective increase of NMDA-sensitive glutamate binding in the striatum of Parkinson's disease, Alzheimer's disease, and mixed Parkinson's disease/Alzheimer's disease patients: an autoradiographic study

Abstract: Parkinson's disease (PD) and Alzheimer's disease (AD) may share certain abnormalities since a subset of PD patients suffer from dementia, and some AD individuals show extrapyramidal symptoms. In vitro quantitative autoradiography was used to examine different subtypes of excitatory amino acid (EAA) receptors (NMDA, KA, and AMPA) and dopamine transporter sites in the striatum (caudate, putamen) and nucleus accumbens (NAc) from idiopathic PD, pure AD, and mixed PD/AD patients. PD and AD groups, and to a lesser e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 40 publications
2
42
1
1
Order By: Relevance
“…NMDA receptors located in human cortical (Conti et al 1997), striatal (Ulas et al 1994), and cerebellar (Jansen et al 1991) regions might be functionally important for smooth pursuit. Ketamine antagonism of NMDA receptors in any of these areas may have been responsible for the portion of the smooth pursuit impairment not attributable to frank nystagmus.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptors located in human cortical (Conti et al 1997), striatal (Ulas et al 1994), and cerebellar (Jansen et al 1991) regions might be functionally important for smooth pursuit. Ketamine antagonism of NMDA receptors in any of these areas may have been responsible for the portion of the smooth pursuit impairment not attributable to frank nystagmus.…”
Section: Discussionmentioning
confidence: 99%
“…lamotrigine). A study also has reported increased NMDA-sensitive glutamate binding in the striatum of Alzheimer and Parkinson patients [20], further indicating a role for glutamate excitotoxicity in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 94%
“…Glutamatergic activity and NMDA receptor density in the basal ganglia increase in patients with PD (23). Cycloserine is able to pass blood-brain barrier and enter the brain tissue where it acts as a partial agonist by binding to the binding site of the NMDA receptor (9).…”
Section: Discussionmentioning
confidence: 99%